Literature Study: Character Values of National Spirit of Students in Elementary Schools - Nur Marsita; Phrapalad Somchai Damnoen; Dong Anh Chi Hong (Journal of Basic Education Research, 2023)
Purpose of the study: This study aims to look at the character values of the national spirit of elementary school students Methodology: The review method was chosen to obtain research journals with national spirit characters keywords on Google undergraduate reference sources. Twenty-five journals were reviewed based on the author (year), article name, title, and findings. Main Findings: The results of the review show a character value of national spirit in students, especially students in elementary schools. This character can be seen from the results of the articles reviewed. Novelty/Originality of this study: This research can contribute to the world of education, especially in looking at the character values of students.